1992
DOI: 10.1209/0295-5075/18/3/007
|View full text |Cite
|
Sign up to set email alerts
|

High Resistivity and Diamagnetism in AlPdMn Icosahedral Phase

Abstract: PACS. 61.40 -Amorphous and polymeric materials. PACS. 72.15C -Electrical and thermal conduction in amorphous and liquid metals and PACS. 75.203 -Metals and alloys. alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
0
2

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(66 citation statements)
references
References 13 publications
11
53
0
2
Order By: Relevance
“…The overall behavior with a comparatively flat maximum at intermediate temperatures of order 50-100 K is in agreement with previous reports on single-as well as polygrained i-Al-Pd-Mn. [2][3][4][5][6]8 With some scatter for the samples at intermediate positions, it can be seen from Fig. 2 that there is a clear trend for a stronger temperature dependence and an increasing maximum in (T)/(300 K) when moving in the growth direction from top to bottom of the sample, together with a weak tendency for a decreasing temperature of the maximum resistivity in the same sequence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The overall behavior with a comparatively flat maximum at intermediate temperatures of order 50-100 K is in agreement with previous reports on single-as well as polygrained i-Al-Pd-Mn. [2][3][4][5][6]8 With some scatter for the samples at intermediate positions, it can be seen from Fig. 2 that there is a clear trend for a stronger temperature dependence and an increasing maximum in (T)/(300 K) when moving in the growth direction from top to bottom of the sample, together with a weak tendency for a decreasing temperature of the maximum resistivity in the same sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Although work on single grained i-Al-Pd-Mn show similar maxima, [2][3][4][5][6] results for polygrained samples indicate that such a maximum may depend on annealing conditions and on Mn concentration, 3,8 with a tendency for this maximum to develop with decreasing Mn concentration below about 10 at. % and to be suppressed again below about 8 at.…”
Section: A Resistivitymentioning
confidence: 99%
See 1 more Smart Citation
“…A striking example are magnetic properties of icosahedral i-Al-Pd-Mn QCs, where a study [2] of a large number of samples with the Mn concentration in the range between 7.5 and 8.6 atomic %, showing different morphologies (single-crystalline and polygrain) and subjected to different thermal treatments (annealing temperature and time, followed by either RC or SC cooling mode to RT), has reported that the magnetic Mn fraction in the samples varies over two orders of magnitude (from 3.8 Â 10 -5 to 2 Â 10 -3 ). Thermal annealing resulted in a reduction of the magnetization by as much as a factor of 8 [3,4]. It was also demonstrated [5,6] that the choice of the cooling rate after the annealing period strongly affects the magnetization of the i-AlPd-Mn QCs in a reversible way, with slowly cooled samples being systematically less magnetic than the rapidly cooled ones.…”
Section: Introductionmentioning
confidence: 93%
“…In i-AlPdMn, single-grains with conductivities as low as that found in best quenched and annealed i-AlPdMn ribbons [25] was a many year effort. Not only chemical composition tuning but also single-grains post-growth annealing are crucial [26].…”
Section: Single-grains Versus Polycrystalline Samples: Effect Of Annementioning
confidence: 99%